Hubungan Dukungan Keluarga Dengan Prestasi Belajar pada Anak Retardasi Mental di SDLBN Bangkinang Kota Tahun 2022 - Umami, Ulfa; Syarif Hamidi, M. Nizar; Nur Afrinis (JHN: Journal of Health and Nursing, 2023)
The worldwide prevalence of Mental Retardation (RM) is estimated at 2.3% of the entire population. The purpose of this study is the relationship between family support and learning achievement in SDLBBN Bangkinang Kota children in 2022. The total population is all parents of children with mental retardation grades I-VI at SDLB Bangkinang Kota with a total of 45 people for the 2022 period. The sample in the study This is part or representative of the population to be studied. The sampling technique uses total sampling. Measuring tool used is a questionnaire. The analysis used was univariate and bivariate, chi-square test. Based on the results of a study of 45 mothers who had children with mental retardation, most of the family support was not good, as many as 27 people (60%), the learning achievements of children with mental retardation were good, as many as 24 people (53.3%). Based on the statistical test with the chi-square test, it is obtained that p value = 0.001 ≤ (0.05) with a 95% confidence level, then Ho is rejected, which means it is significant. This means that there is a relationship between family support and learning achievement in children with mental retardation at Bangkinang City SDLBN in 2022. It is hoped that the results of this study can provide basic material for families to provide support to their children.